An experimental study on the oil-soluble surfactant-assisted cyclic mixed solvent injection process for heavy oil recovery after primary production. (15th October 2019) - Sun, Xiaofei; Zhao, Hao; Zhang, Yanyu; Liu, Yunlong; Chen, Guangpeng; Wang, Wenhui
Graphical abstract: Highlights: The OSFA-CMSI process is a potentially feasible method for heavy oil recovery. The designed setup can better study CSI-based processes under reservoir conditions. The OSS plays a more important role than C3 H8 in the OSFA-CMSI processes. The solvent mixture should be injected at or near to its dew point conditions. The OSFA-CMSI process may be more suitable to post-CHOPS reservoirs. Abstract: Cyclic solvent injection (CSI) has shown a significant potential to enhance heavy oil recovery after primary production. However, the principal limitation of this process is quick solvent liberation due to the high gas mobility and oil viscosity regainment during the production period. In this study, a novel variation of CSI, called oil-soluble surfactant-assisted cyclic mixed solvent injection (OSFA-CMSI), is proposed to overcome these limitations. During this process, an oil-soluble surfactant and a specially designed solvent mixture (produced gas and propone) are cyclically injected into reservoirs in two separate slugs. The designed solvent mixture renders the process technically sound and effectively viable, and the surfactant induces the formation of an effective foamy oil flow by dispersing the released or undissolved gaseous solvent during the production period. A series of experiments were performed by using a patented core holder to prove the viability of the OSFA-CMSI process and to study the effects of the solvent composition, pressure depletion rate, wormhole presence, and confining pressure on the OSFA-CMSI performance. The experimental results show that the selected oil-soluble surfactant FlourN™ 20158M can create an effective foamy oil phenomenon in heavy oil, which contributes to the enhanced oil swelling effect and gas dispersion that delays the formation of free gas. The OSFA-CMSI process is a potentially feasible method for heavy oil recovery after primary production, especially for post-cold heavy oil production with sand reservoirs. The most efficient test improves oil recovery by 41.64% of the original oil in place (OOIP) compared to that of the traditional CSI process. There is an optimal C3 H8 content in the solvent mixture (46 mol% in this study), beyond which the performance of the OSFA-CMSI process worsens. The solvent mixture should be injected at or near its dew point without any liquefaction to achieve maximum solubility and generate an effective foamy oil flow. Increases in the pressure depletion rate and confining pressure are beneficial when using OSFA-CMSI to enhance the oil recovery factor over a short production time but result in lower final oil recovery factors.